Case report: Obstructive azoospermia as the first presentation of Von Hippel-Lindau disease - Scafa, Raffaele; Merico, Maurizio; Ferrara, Alfonso Massimiliano; Watutantrige Fernando, Sara; Srsen, Pava; Schiavi, Francesca; Zovato, Stefania; Ferlin, Alberto (Frontiers in Oncology, 2023)
We report a case of a 38-year-old man whose diagnostic work-up for primary infertility led to the discovery of obstructive azoospermia due to bilateral papillary cystadenoma of the epididymis (PCE). Given the rarity of the finding and since PCE might be a manifestation of Von Hippel Lindau disease (VHL), although the patient had no family nor personal history of VHL, VHL gene was tested and a known pathogenetic variant (c.464-1G>A; p.?) was found. The screening for other Von Hippel Lindau disease-associated neoplasms found bilateral retinal capillary hemangioblastomas, clear cell renal cell carcinoma and many pancreatic cysts. In this case, an accurate diagnostic work-up for male infertility allowed the detection of a rare life-threatening syndrome, already presenting with several silent neoplasms. For this reason, this case report can be useful for specialists in the field of reproductive medicine in the management of male infertility.